EFL TEACHER’S USE OF MULTIPLE APPLICATIONS IN ONLINE LEARNING DURING COVID-19 PANDEMIC - Dery Athama Putra; Eusabinus Bunau; Sumarni Sumarni (Universitas Tanjungpura, 2022)
The research aimed to describe how an EFL teacher used multiple applications namely WhatsApp, Google Classroom, Google Forms, and Quizizz in online learning during COVID-19 pandemic and what kind of activities the EFL teacher did on each application to enhance her students’ English skills. The subject of this research was an EFL teacher from SMA Negeri 8 Pontianak who had taught online since 2020. A case study design was employed in this research by using semi-structured interview, observation, and document analysis as the method of data collection. The results revealed that, the EFL teacher could teach and deliver courses during the online learning session without the use of video conferencing applications such as Zoom and Google Meet. The EFL teacher used WhatsApp, Google Classroom, Google Forms, and Quizizz for a variety of purposes, including verifying students' attendance and conducting assessments. The activities used to enhance the students’ English skills were reading comprehension tasks on Quizizz, listening comprehension tasks on Google Forms and Quizizz, paragraph or conversation writing activities on Google Classroom, as well as video recording activities on Google Classroom.